Hubungan Intensitas Kebisingan Lalu Lintas dengan Stres Kerja pada Petugas Parkir di Jalan Prof. H. M. Yamin Medan Tahun 2013 - ahmad fauzi nasution (Lingkungan dan Kesehatan Kerja, 2014)
Prof. H. M. Yamin streets is the main street passed by many vechhiles. This road is surrounded buildings. Which as public place such as a hospital, food store, mosque and offices place, so that potentially cause noise that exceeds the threshold values which have been determinate. This research aims to know intensity of noise, relations intensity of noise with job stress, noise intensity relationship with job stress based on age and employment history. This types of research is survey analytic by cross sectional design. The population is all parking attendants around Prof. H.M.. Yamin streets, Medan as many as 30 people and made entirely of samples. The object of this research was the traffic noise obtained from the measurement results directly and interviews. The results of this research indicate the intensity of traffic noise in point 1 in front of Al-Amin’s mosque, is  (82,96 dB/A), while traffic noise intensity in point 2 in front of the Pirngadi Hospital Medan is (80,53 dB/A). There was no significant relation between age (p = 0.364), work time (p = 0.073),longer work (p=0,140) and traffic noise intensity (p = 0,624) and work stress on street parking officer Prof. H.M. Yamin street, Medan. Suggested to relevant agencies to conduct health checks at regular intervals, to the parking attendants to that regular meals, adequate rest, confident, sociable, positive thinking, and reduce cigarette consumtion / coffe, and should be done in order to shift the parking attendants do not get exposure to noise on and should be done in order to shift turnover parking attendants got no exposure to noise. Keywords : Intensity of Noise, Job Stres, Parking Attendant